Evaluation of universal design for constructivist-based statistics learning module for students’ increased motivation - Rufii Rufii; Dyah Rochmawati (Intelektual Pustaka Media Utama, 2019)
This exploratory study was aimed at evaluating a module on the basis of the constructivist learning strategies to enhance the students’ motivation in Statistics learning. The design and development followed the Universal Design of Learning principles. The design included flexible instructional materials, techniques, and strategies for differentiating instruction which benefited the students of English Education Department taking the Statistics course. The study used a survey covering of 33 students. The students’ and teacher’ responses to questionnaires revealed that the students’ motivation and satisfaction increased toward the Statistics course in which Universal Design of Learning using various means of representation, action, and engagement was applied. It also suggested that the module was effective and that the Universal Design of Learning Model from the learners’ viewpoint put more emphasis on instruction. Its content was suitable in designing and developing module on Statistics in the higher educational context in Indonesia. The study results are expected to reveal information on how to further improve the Statistics teaching and learning quality. The implications of the researchare provided along with suggestions.This exploratory study was aimed at evaluating a module on the basis of the constructivist learning strategies to enhance the students’ motivation in Statistics learning. The design and development followed the Universal Design of Learning principles. The design included flexible instructional materials, techniques, and strategies for differentiating instruction which benefited the students of English Education Department taking the Statistics course. The study used a survey covering of 33 students. The students’ and teacher’ responses to questionnaires revealed that the students’ motivation and satisfaction increased toward the Statistics course in which Universal Design of Learning using various means of representation, action, and engagement was applied. It also suggested that the module was effective and that the Universal Design of Learning Model from the learners’ viewpoint put more emphasis on instruction. Its content was suitable in designing and developing module on Statistics in the higher educational context in Indonesia. The study results are expected to reveal information on how to further improve the Statistics teaching and learning quality. The implications of the researchare provided along with suggestions.